AKTIVITAS DAN ISOLASI SENYAWA BIOAKTIF DARI EKSTRAK ETIL ASETAT DAUN TEH (Camellia sinensis (L.) Kuntze) SEBAGAI PENGHAMBATAN ENZIM α-GLUKOSIDASE - Nuraini Saadah; Lilik Sulastri; Syamsoedin Abdilah; Partomuan Simanjuntak (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
Tea (Camellia sinensis (L.) Kuntze) is one of the plants that has compounds that have the potential as inhibitors of the α-glucosidase enzyme. The purpose of this study was to know the activity of chemical compounds in the ethyl acetate extract of tea leaves as an inhibitor of the α-glucosidase enzyme. Extraction tea leaf was carried out by maceration tea leaf powder in ethanol 96% 3 times, then partitioned with ethyl acetate and water. The ethyl acetate extract obtained was determined by the inhibitory activity of the -glucosidase enzyme, then fractionated by column chromatography (SiO2; n-hexane: ethyl acetate 10:1 1:1) yielding 10 fractions (CSEA-1 CSEA-10). The CSEA-2 fraction was further fractionated by column chromatography (SiO2; n-hexane: ethyl acetate 20:1 1:1) yielding 9 fractions (CSEA-2.1 CSEA-2.9). The results showed that the ethyl acetate extract had activity with an IC50 value of 45.04 ppm, the fractionated CSEA-2.1 subfraction had an IC50 value of 41.51 ppm with acarbose as a comparison of 19.24 ppm. The conclusion is that the CSEA-2.1 subfraction has better activity than the extract in inhibiting the α-glucosidase enzyme and can be used as an alternative candidate for diabetes drugs. Keywords: Camellia sinensis (L.) Kuntze, tea, α-glucosidase enzyme inhibitor, Indonesian medicinal plant, IC50